2022
DOI: 10.1111/pce.14386
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of plant development and chilling stress responses by alternative splicing events under control of the spliceosome protein SmEb in Arabidopsis

Abstract: Cold stress resulting from chilling and freezing temperatures substantially inhibits plant growth and reduces crop production worldwide. Tremendous research efforts have been focused on elucidating the molecular mechanisms of freezing tolerance in plants. However, little is known about the molecular nature of chilling stress responses in plants. Here we found that two allelic mutants in a spliceosome component gene SmEb (smeb‐1 and smeb‐2) are defective in development and responses to chilling stress. RNA‐seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…However, overexpression of SmEb is unable to improve salt resistance in transgenic plants (Figure S6), suggesting a possible tissuespecific function of SmEb required for salt stress response. This notion is in accordance with the finding that the phenotype of smeb mutant plants can be recovered by expressing SmEb promoter-driven SmEa gene which encodes for another SmE protein (Wang et al, 2022). LSM8 and SmD3b are two spliceosome proteins essential for plants, but only SmD3b plays a role in salt stress response (Figure 2C, D).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, overexpression of SmEb is unable to improve salt resistance in transgenic plants (Figure S6), suggesting a possible tissuespecific function of SmEb required for salt stress response. This notion is in accordance with the finding that the phenotype of smeb mutant plants can be recovered by expressing SmEb promoter-driven SmEa gene which encodes for another SmE protein (Wang et al, 2022). LSM8 and SmD3b are two spliceosome proteins essential for plants, but only SmD3b plays a role in salt stress response (Figure 2C, D).…”
Section: Discussionsupporting
confidence: 90%
“…To elucidate the role of SmEb in salt stress response, we performed transcriptome analysis using smeb‐1 , smeb‐2 , and Col‐0 seedlings treated with 150 mM NaCl for 6 h. Under normal growth conditions, 55 differential alternative splicing events of 27 genes were identified in smeb mutants compared to the wild type (Wang et al, 2022). Under salt stress condition, 634 differential alternative splicing events of 375 genes were identified in smeb mutants, while 497 differential alternative splicing events of 441 unique genes occurred in the Col‐0 plants (Figure 3A, B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, the AS of SmEb has been associated with plant cold stress. 17 Previous research categorizes AS into seven main types: Alternative 3′ splice site (A3), Alternative 5′ splice site (A5), Alternative First exon (AF), Alternative Last exon (AL), Mutually exclusive exon (MX), Retained intron (RI), and Skipping exon (SE). 18 Cyclophilins (CYPs) are members of the peptidyl-prolyl cistrans isomerase family.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another study demonstrated that the AS-related gene Sm core protein SmEb enhances salt tolerance in Arabidopsis thaliana by regulating the AS of pre-mRNA of RCD1 . Furthermore, the AS of SmEb has been associated with plant cold stress . Previous research categorizes AS into seven main types: Alternative 3′ splice site (A3), Alternative 5′ splice site (A5), Alternative First exon (AF), Alternative Last exon (AL), Mutually exclusive exon (MX), Retained intron (RI), and Skipping exon (SE) …”
Section: Introductionmentioning
confidence: 99%